The Development of Thematic Fun Thinkers Flash Card Media in Improving Scientific Thinking Skills for Second Graders of Elementary Students - Mustafa Habib; Zulham Siregar; Elisa Haddina (research, training and philanthropy institution Natural Aceh, 2023)
This research was motivated by the learning process, which still tends to use the explanation method on the material theme of the environment. The learning objectives have not been achieved optimally, affecting student learning effectiveness. One effort that can be used is by using Flash Card Fun Thinkers media. This study used a research and development (R&D) methodology. Flash Card Fun Thinkers media is based on ADDIE's development steps. The population in this study were 33 Second Graders of Elementary students at SD IT Iqro Stabat. The results of the research showed; (1) the material expert validity test scored 92% and was categorized very well, (2) the media expert validity test scored 86.67%, and it was said as in excellent qualifications, (3) the second graders of Elementary teachers’ validity test score was 90%, and it was said in excellent qualifications, (4) individual trials score was of 91.11%, and it was said in excellent qualifications, Small Group trials score was of 90.13%, and it was said in excellent qualifications, Large Group trials score was 88 % and it was said in excellent qualifications. The results showed a significant difference between the learning outcomes of students taught using the thematic Flash Card Fun Thinkers learning media and the conventional learning media.